Umbrales culturales en la dramaturgia del coreano Choi In-Hun - Báez Ayala, Susana (El Colegio de México, 2022)
This article analyzes the dramaturgy in Choi In-Hun’s trilogy: Three Plays (2007), considering Byung-Chul Han’s approach to placing ourselves in the threshold of the (un)known through textual analysis that explores the concept of hypertextuality as a libertarian structure for those who position themselves at cultural thresholds. Referring to Korean culture, this region, and Choi In-Hun’s dramaturgy from the deixis built according to the Latin America’s predominantly Westernized gaze, this study highlights how the works enable the (re)cognition of the strength of the rituals that structure Choi In-Hun’s plays, communities’ capacity to avoid losing diversity, and Korean literature’s approach to sociocultural complexity by exposing the diversity in human relationships.